PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN SATWA YANG DILINDUNGI DI WILAYAH HUKUM KABUPATEN BENER MERIAH - Wiwin Widiarti; Putri Kemala Sari; Apri Rotin Djusfi; Nila Trisna (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Law enforcement against tiger trafficking is a form of tiger protection carried out by the government. In upholding this law, it is necessary to have cooperation between law enforcement officers and the community so that it can minimize the crime of tiger trafficking and can be immediately followed up if someone commits a crime of tiger trafficking in Bener Meriah Regency. This research is an empirical legal reseach which is a reseach using a qualitative approach and descriptive reseach analysis. . As for the purpose of this study is to determine whether law enforcement against tiger trafficking in Bener Meriah Regency has been carried out properly in accordance with the prevailing laws. Law enforcement carried out by the Bener Meriah Regency government is in accordance with the applicable provisions, namely Law Number 8 of 1981 concerning the Criminal Procedure Code and Law Number 5 of 1990 concerning Natural Resources Conservation and in accordance with the international convention cites (Convention on International Trade in Endangered Species of Wild Fauna and Flora).